Reports of Doses Administered and Adverse Reactions to Snake Antivenom Used in Uruguay in 2018 - Negrin, Alba; Battocletti, María Alejandra; Juanena, Carolina; Morais, Victor (Frontiers in Toxicology, 2021)
In Uruguay, around 60 cases of snakebite accidents occur every year that need to be treated with specific antivenom. They are caused by two snakes of Bothrops genus: Bothrops alternatus and Bothrops pubescens. Snakebite accidents are mandatory notification events, allowing the acquisition of an accurate registry and a fluent communication with the health care services. The aim of this study is to analyze and report the doses administered to achieve the neutralization of the venom and the adverse reactions caused by snake antivenoms used in Uruguay in 2018, when a change was made in the type of antivenom available. In this year, Uruguay started to use the BIOL® antivenom (lyophilized) and this use coexists with traditional antivenom liquid forms (Vital Brazil and Malbran). The number of patients treated with heterologous BIOL® antivenom were 28 and the ones treated with heterologous solutions Malbran and Vital Brazil antivenoms were 21. The initial dose of BIOL antivenom was 8 vials instead of 4 vials regularly used with the others antivenoms and it achieved the neutralization of most cases (27/28 cases). Early adverse reactions were detected in 4 patients (3 in children) treated with BIOL antivenom and there were no adverse reactions in those treated with Malbran or Vital Brazil antivenoms. Lyophilized antivenom BIOL is being used widely in Uruguay without major complications.